Tailoring the degradation rate of magnesium through biomedical nano-porous titanate coatings - Matthew D. Wadge; Jamie McGuire; Benjamin V.T. Hanby; Reda M. Felfel; Ifty Ahmed; David M. Grant (Journal of Magnesium and Alloys, 2021)
A novel approach was developed to reduce the corrosion rate of magnesium (Mg) metal, utilising titanate coatings. Magnetron sputtering was used to deposit ca. 500 nm titanium (Ti) coatings onto pure Mg discs, followed by hydrothermal conversion and ion exchange reactions to produce sodium and calcium titanate coatings. SEM confirmed the characteristic nanoporous structure of sodium and calcium titanate, with thicknesses ranging from ca. 0.8 to 1.4 µm. XPS analysis confirmed the presence of Ti4+—O, Na—O, and Ca—O bonding, whilst Raman spectroscopy demonstrated characteristic vibrational modes (such as TiO6 octahedral vibrations) of the sodium and calcium titanate perovskite structure. Furthermore, corrosion studies through potentiodynamic polarisation measurements demonstrated the NB/NH CaTC samples to be superior in reducing Mg degradation, compared to other samples tested, through an increase in Ecorr from −1.49 to −1.33 V, and the reduction in corrosion current density, icorr, from 0.31 to 0.06 mA/cm2 for Mg and NB/NH CaTC samples, respectively. There was a clear trend noted for the NB/NH samples, which showed an increase in Ecorr to more positive values in the following order: Mg < Ti coated < NaTC < CaTC. These nanoporous titanate coatings have potential to be applied onto degradable plates for bone fracture fixation, or other orthopaedic applications.